The Mystery of Existence: on How to Experience the World in Joseph Weyssenhoffs Sable and the Lady - Pietrasik, Patrycja (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The aim of the article is to show what are the characters of Joseph Weyssenhoff’s Sable and the lady perceptions of the world. It addresses the specificity of the descriptions of nature, which undoubtedly affect the characters of the novel. A great part of the novel is devoted to the relations between humans and nature, which indicates that there exists a special bond between them. On the basis of the reflections mentioned in the novel we observe a sort of connection between the environment and human life. We can distinguish similarities in terms of character creation and their surroundings, as well as highlighting important elements such as personification of the descriptions of nature and animals, the influence of nature on the feelings and behavior of the characters, which often varies along with changes of their mood; poetic thoughts influenced by the contemplation of nature, the presence of fauna and flora in the most important events of the characters’ lives.